2014
DOI: 10.5455/2319-2003.ijbcp20140214
|View full text |Cite
|
Sign up to set email alerts
|

Crude ethanolic leaf extracts of Citropsis articulata: a potential phytomedicine for treatment of male erectile dysfunction associated with testosterone deficiency

Abstract: Citropsis articulata, also locally known as the Omuboro is a popular plant in Central and Western Uganda for its claimed aphrodisiac properties. The plant naturally grows in forests and locals uproot it to obtain the roots for treatment of erectile dysfunctions. The root of this plant has been cherished as one of the most valuable herbal Viagra by most rural communities in Uganda. 1 The fast disappearance of these culturally important medicinal plants due to poor utilization practices certainly pose major thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
(4 reference statements)
1
6
1
Order By: Relevance
“…This result thus indicates that the aqueous extract of T. graveolens could be useful in treatment of those with erectile dysfunction resulting from hypogonadism. More so, the increase in testosterone levels indicated by the aqueous extract of T. graveolens did not correspond to the mounting frequency, contrary to many reports including (Vudriko et al, 2014;Oloro et al, 2014). The extract of T. graveolens as indicated in this study could be improving sexual activity in men with suspected erectile dysfunction by increasing their testosterone level.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This result thus indicates that the aqueous extract of T. graveolens could be useful in treatment of those with erectile dysfunction resulting from hypogonadism. More so, the increase in testosterone levels indicated by the aqueous extract of T. graveolens did not correspond to the mounting frequency, contrary to many reports including (Vudriko et al, 2014;Oloro et al, 2014). The extract of T. graveolens as indicated in this study could be improving sexual activity in men with suspected erectile dysfunction by increasing their testosterone level.…”
Section: Discussioncontrasting
confidence: 73%
“…Although mounting was noted in some of the animal groups treated, the results were not statistically significant in comparison to those of the control groups (Table 2). Despite the presence of arginine and saponins in the extract and their being reported as substance known to regulate erectile function and increase in testosterone levels respectively T. graveolens at the dose of 250 mg/kg significantly increased testosterone levels in males rats (Table 3) more than that reported for Citropsis articulata leaf extract (Vudriko et al, 2014) and Citropsis articulata root bark extract (Oloro et al, 2014). Although not quantitatively determined, the increase in testosterone levels could suggest that there was a higher level of saponins in the extract of T. graveolens (Koumanov et al, 1982).…”
Section: Discussionmentioning
confidence: 78%
“…The increased testosterone levels noted with the dose at 1000 mg/kg and the significant effects on mounting noted at the same dose could probably be indicating that, the aqueous extract of C. articulata improves sexual function by increasing testosterone levels, similar to the result found by Vudriko et al (2014) on the leaf extract of C. articulata on male rats. The testosterone levels noted in this case were however, lower than the results obtained from the use of A. polycantha ethanolic stem bark extract by Wawata et al (2010), but were much higher than that reported by El-Tantawy et al (2007) on the effects of Tribulus alatus extracts on free serum testosterone levels.…”
Section: Discussionsupporting
confidence: 60%
“…This ethnobotanical indigenous knowledge has not been earlier documented and scientifically validated for efficacy and safety, future drug discovery and development (Kamatenesi-Mugisha and Oryem-Origa, 2005). Available information indicate that the leaf extract of C. articulata improves testosterone levels and could be used to treat erectile dysfunction in men with low testosterone levels (Vudriko et al, 2014), but no data exist about the root extract which has been used for ages.…”
Section: Introductionmentioning
confidence: 99%
“…Citropsis articulata is usually a shrub or small tree, ranging from 2.5 to 5 m in height but sporadically much taller [1,3]. is plant species is well known for its aphrodisiac properties, and recent studies have proven its antiplasmodial potential too [4,5]. Unfortunately, the plant part used for its medicinal purpose is the root and thus the most harvested, and this could endanger its existence.…”
Section: Introductionmentioning
confidence: 99%